Inovasi Pembelajaran di Masa Pandemi Covid-19 - Rahmah, Nurul Wahidatur; Rahman, Sawaludin; Amin, Alfauzan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This article aims to examine and discuss innovations in learning that took place during the Covid-19 pandemic. Use of literature review techniques together with qualitative research strategies. To collect data, researchers looked at various sources, including official government newspapers, news, and relevant study findings that had been investigated using policy research and confirmed by results of interviews with students and teachers concerned. The research results obtained were carried out content analysis for information checking. The results of the study show that the development of innovation is influenced by the government's efforts to control the spread of the corona virus (Covid-19). aimed at the advancement of useful learning. These educational innovations include blended learning, learning as an opportunity and challenge, and learning from home: collaboration between parents and schools. Existing innovations were developed during the Covid 19 pandemic. In order for children to get a good education and be able to compete on a global scale, parents, educators and the government must all work together. In conclusion, after the Covid-19 outbreak has passed, it is hoped that innovation in technology-based education will continue, thus enabling the adoption of higher quality education. To achieve effective and efficient education in dealing with current world disease problems, it is highly recommended that parents, teachers and the government collaborate. Keywords: Innovation, Learning, Corona Virus (COVID-19)